2023
DOI: 10.3390/su152115234
|View full text |Cite
|
Sign up to set email alerts
|

Economic Sustainability of the Milk and Dairy Supply Chain: Evidence from Serbia

Dragan Milić,
Tihomir Novaković,
Dragana Tekić
et al.

Abstract: The sector of milk and dairy products in Serbia along the entire supply chain has been under significant challenges in recent years, especially in current crises. In this direction, this research looked at the supply chain of milk and dairy products by analyzing the primary production, the situation in the processing industry, and the international market’s competitiveness. Indicators of technical efficiency were used to analyze the situation on agricultural farms, while for the processing industry, the impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Ref. [15] showed that the steady intensification of the aspect of economic sustainability leads both to an increase in the level of technical efficiency of undertakings producing milk as well as the general improvement of the life of the whole community. Ref.…”
Section: Economic Sustainability Of the Supply Chain (Ecsc)mentioning
confidence: 99%
See 1 more Smart Citation
“…Ref. [15] showed that the steady intensification of the aspect of economic sustainability leads both to an increase in the level of technical efficiency of undertakings producing milk as well as the general improvement of the life of the whole community. Ref.…”
Section: Economic Sustainability Of the Supply Chain (Ecsc)mentioning
confidence: 99%
“…Thirdly, the study contributes to theoretical and empirical research on sustainable management of supply chains in secondary emerging countries, such as Romania. In recent years, the attention of managers and researchers has generally focused on the economic sustainability of the supply chain and its effect on financial performance [11][12][13][14][15]. This research focuses equally on the three elements of supply chain sustainability and practices that should be improved to cope with future disruptions, as well as to strengthen the performance of enterprises from this system.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, China has a vast territory, and there are differences in economic and technological development levels, resource endowment and culture among different provinces, leading to obvious provincial disparities in the green development of the dairy industry [5]. In this context, how to accelerate the green and coordinated development of the dairy industry has become an important topic of concern for academic circles and decision-making departments [6]. Therefore, this paper calculates the green development characteristics and influencing factors of China's dairy industry in various provinces through green total factor productivity, which has important practical significance for the realization of high-quality sustainable development in China's dairy industry.…”
Section: Introductionmentioning
confidence: 99%